2017
DOI: 10.1590/1678-4685-gmb-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic history of South American populations of the silky anteater Cyclopes didactylus (Pilosa: Cyclopedidae)

Abstract: Cyclopes didactylus, commonly called silky anteater, is the smallest and least studied of the anteaters. It is an arboreal species occurring in rainforests, ranging from southern Mexico to Central and South America, with an apparently disjoint distribution between Amazon and Atlantic rainforests in Brazil. Although seven subspecies are recognized, little is known about its geographical variation. Thus, to evaluate the population dynamics and evolutionary history of the South American silky anteater, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…Given the geographic distribution of each identified lineage, and the general branching of the tree topology, the results agree with the geological history of the Andean mountains in Northwestern South America and support previously proposed models of ichthyofauna division, based on several species-level phylogenies (Albert, Lovejoy & Crampton, 2006). Patterns of divergence, in concordance with the geological evolution of Northwestern South America found in this study, have also been reported in other fishes (Hernández et al, 2015;Machado, Galetti & Carnaval, 2018;Rincón-Sandoval, Betancur & Maldonado-Ocampo, 2019) and other taxa such as mammals (Coimbra et al, 2017) and insects (Salgado-Roa et al, 2018;Bartoleti et al, 2018). In addition, our results support a north to south uplift of the Colombian Andes (Florez, 2003), as diversification of Pseudopimelodus occurred in a sequential manner from older lower altitude diversification events to younger higher altitude diversification events, as was also reported in Neotropical plant species in Colombia (Richardson et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Given the geographic distribution of each identified lineage, and the general branching of the tree topology, the results agree with the geological history of the Andean mountains in Northwestern South America and support previously proposed models of ichthyofauna division, based on several species-level phylogenies (Albert, Lovejoy & Crampton, 2006). Patterns of divergence, in concordance with the geological evolution of Northwestern South America found in this study, have also been reported in other fishes (Hernández et al, 2015;Machado, Galetti & Carnaval, 2018;Rincón-Sandoval, Betancur & Maldonado-Ocampo, 2019) and other taxa such as mammals (Coimbra et al, 2017) and insects (Salgado-Roa et al, 2018;Bartoleti et al, 2018). In addition, our results support a north to south uplift of the Colombian Andes (Florez, 2003), as diversification of Pseudopimelodus occurred in a sequential manner from older lower altitude diversification events to younger higher altitude diversification events, as was also reported in Neotropical plant species in Colombia (Richardson et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Hence, sampling deficiencies in the north-eastern dry diagonal, in addition to the non-inclusion of specimens deposited in museum collections or published records of species in this region [ 24 ] may have led to faulty estimates of the number of potential taxa that could have spread along the Eastern route. As new records appear with increased sampling effort through systematic biogeographic studies in this region, future reassessments will thus, almost certainly, find additional species, which evidence past dispersions along the Eastern route [ 69 73 , 76 ]. For example, several recent studies have presented new records of common forest species, such as for marsupials [ 74 77 ] and rodents [ 78 , 79 ] along the Eastern route.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed as mammals (Coimbra et al, 2017) and insects (Salgado-Roa et al, 2018;Bartoleti et al, 2018).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%